Application of a hybrid approach to the design of anchored wire meshes on steep slopes - Galli, A; Deana, M; Mazzon, N (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Anchored steel meshes are commonly employed stabilising systems for potentially unstable granular layers (e.g. soil or highly fragmented weak rock) on slopes against translational failure mechanisms. They are usually conceived as passive stabilising intervention (i.e. their stabilising action is provided only upon the activation of a given displacement field into the unstable layer). As a consequence, standard design methods, generally based on ultimate limit state (ULS) approaches, can potentially be largely unsafe, since they assume the full mobilisation of both the ultimate soil resistance and the ultimate tensile force in the steel mesh independently of the displacement amplitude of the unstable layer. In this paper a design procedure, based on so called ‘hybrid’ approaches, is described with specific reference to relatively steep slopes. The key concept is the use of a suitable characteristic curve, describing the mechanical response of the entire system (steel plate, steel mesh, soil layer) as a function of the displacement amplitude, thus providing a safe and consistent estimation of the mobilised stabilising action for the required safety level.
Keywords: anchored steel meshes; design procedure; hybrid methods